Do Thai foods outshine Malaysian food locally and internationally? / Zulhan Othman ...[et al.] - Othman, Zulhan; Salehuddin, Mohd; Hashim, Rahmat; Ibrahim, Shahariah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
This empirical study investigated to what extent the local restaurant customers accept Thai food. In addition, this study also evaluated any changes in customers’ eating patterns of local cuisines. Restaurant customers in the Shah Alam area were selected as a sample. One notable finding was that respondents saw a trend towards Thai foods which are becoming well accepted in this country. Nevertheless, despite the increasingly popularity of Thai food it was not to the extent of outshining the local food. Thai foods were found to be not consumed everyday by the local people, but rather as an option or alternative or as part of leisure dining. Another interesting issue and in fact the most remarkable finding of this study was that respondents seemed to agree that Thai food is more popular and internationally accepted than Malaysian food. This indication has significant implications for the related authorities as to why Malaysian food is not as popular as Thai food internationally in spite of having a distinctive flavour and diversity of taste.